Combining pH-triggered adsorption and photocatalysis for the remediation of complex water matrices. Issue 5 (October 2022) - Cionti, Carolina; Pargoletti, Eleonora; Falletta, Ermelinda; Bianchi, Claudia L.; Meroni, Daniela; Cappelletti, Giuseppe
Abstract: Adsorption and photocatalysis are water remediation techniques with unique advantages and limitations that can make them complementary: while adsorption is a cheap and fast process that simply transfers the pollutant to another phase, photocatalysis is a slow and costly procedure that however can degrade recalcitrant pollutants. Here, we propose a sequential treatment based on reversible and selective adsorption, followed by heterogeneous photocatalysis. In particular, the reversible and selective adsorption of dye molecules was achieved by polyaniline (PANI)-based hybrid adsorbents. The role of the dye content, adsorbent dose, solution pH and electrolyte composition was investigated. By tuning the adsorption pH, an effective regeneration of the spent adsorbent could be achieved by the triggered release of the adsorbate in an aqueous solution and under mild conditions. Moreover, the separation of multi-dye mixtures (methyl orange and methylene blue) was proven, also in consecutive cycles. The selective recovery of one of the components could enable dye recycling. An ensuing photocatalytic step using a commercial photocatalyst could be adopted to either degrade the leftover solution or the regeneration solution. The release of a single pollutant in aqueous solvent, with controlled composition and tunable concentration, allows performing photocatalysis more efficiently. This combined approach enables a fast and effective treatment of the effluent and an easy regeneration of the spent adsorbent with ensuing treatment of the regeneration solution for a zero-waste strategy. Graphical Abstract: ga1 Highlights: High performing sequential treatment of adsorption and heterogenous photocatalysis. Fast and reversible adsorption of dyes by polyaniline-based hybrids also in electrolyte solution. pH-driven selective adsorption for the separation of multi-dye solutions. Adsorbent regeneration in aqueous solvent and mild conditions with dye recovery. Photocatalytic dyes degradation by ZnO for zero waste strategy.